Sustainability-induced loyalty in festival tourism: Examining the mediating pathways between sustainable practices and visitor behavioral support - Yuanxiang Peng (PLoS ONE, 2026)
This research constructs a comprehensive theoretical framework examining the multidimensional influence mechanisms of music festival sustainability practices (environmental, social, economic dimensions) on visitor behavioral intentions. Based on the integration of sustainable tourism, environmental awareness, perceived value, and tourist satisfaction theories, the study proposes a hypothetical model encompassing both direct and mediating effects. Through a survey of 500 participants at a major international music festival, advanced statistical techniques validate the complex mechanisms through which sustainability practices influence visitor behavioral intentions via multiple pathways. Findings show: (1) all three dimensions of sustainability practices exert significant direct positive effects on behavioral intentions, with environmental sustainability having the strongest influence (β = 0.187, p < 0.001); (2) environmental awareness, perceived value, and tourist satisfaction play significant mediating roles between sustainability practices and behavioral intentions; (3) sustainability practices influence behavioral intentions through sequential mediating pathways of “environmental awareness to perceived value” and “perceived value to satisfaction.” These findings suggest that sustainability practices should be viewed as strategic assets enhancing visitor experiences rather than merely compliance obligations. By refining sequential mediations in a music festival context (extending linear models like VBN), the study addresses a key “black box” in pro-environmental behavior, while providing empirical guidance for organizers to build integrated strategies that promote resilient tourism amid post-COVID recovery and overtourism pressures.